Confronting the Mysteries of Oxidative Reactive Species in Advanced Oxidation Processes: An Elephant in the Room - Wu, Jing-Hang; Yu, Han-Qing (Environmental science & technology, 2024)
Advanced oxidation processes (AOPs) are rapidly evolving but still lack well-established protocols for reliably identifying oxidative reactive species (ORSs). This Perspective presents both the radical and nonradical ORSs that have been identified or proposed, along with the extensive controversies surrounding oxidative mechanisms. Conventional identification tools, such as quenchers, probes, and spin trappers, might be inadequate for the analytical demands of systems in which multiple ORSs coexist, often yielding misleading results. Therefore, the challenges of identifying these complex, short-lived, and transient ORSs must be fully acknowledged. Refining analytical methods for ORSs is necessary, supported by rigorous experiments and innovative paradigms, particularly through kinetic analysis based on spectroscopic techniques and multiple-probe strategies. To demystify these complex ORSs, future efforts should be made to develop advanced tools and strategies to enhance the mechanism understanding. In addition, integrating real-world conditions into experimental designs will establish a reliable framework in fundamental studies, providing more accurate insights and effectively guiding the design of AOPs.